The development of Japan’s international human security diplomacy: towards a “normal” country? - Mohd Ikbal Mohd Huda, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
This article offers an alternative perspective of Japan’s international human security diplomacy concerning the underlying motivations that has caused Japan to pursue its international human security diplomacy in such proactive and aggressive manner. So far Japan’s involvement in the international human security initiatives had only been examined separately in the literature, with not much attention been given towards it linkage with Japan’s relentless efforts and restraints throughout the decades towards becoming a normal state. This article argues that when Japan’s involvement in international human security is studied together with its underlying ambition of becoming a normal state, the approach can no longer be solely understood as Japan’s effort to compensate the imbalances between its reactive international political posture and its significant status as the world’s third-biggest economy. Instead, this involvement should be examined from the perspective of Japan’s own national security requirements. Most importantly, it should be examined alongside Japan’s effort to strategically participate, contribute, and gain greater autonomy in the international political sphere under its envisioned status as a normal country. From this perspective, the motivation behind Japan’s persistence and aggressive pursuit of its international human security diplomacy becomes clearer under Prime Minister Abe’s “proactive contribution to peace”. It implies a shift in Japan’s security identity from a ‘peace state’ to an ‘international state’ that sees Japan playing a more active role in responding to the structural changes of the international security environment. In particular, it corresponds with Japan’s effort under the Abe administration to inculcate worldwide awareness that becoming a “normal state” is a prerequisite for Japan to collaborate with the international community and contribute effectively towards sustainable world peace and stability.